2014
DOI: 10.1177/0892705713518786
|View full text |Cite
|
Sign up to set email alerts
|

Radiation synthesis of superabsorbent hydrogels based on carboxymethyl cellulose/sodium alginate for absorbent of heavy metal ions from waste water

Abstract: Superabsorbent hydrogels based on natural polymer, carboxymethyl cellulose (CMC)/ sodium alginate (SA) were prepared by 60 Co radiation as a source of initiation of crosslinking. The effect of different ratios of SA (20, 30, 40, and 50%) on the physical properties of the CMC/SA hydrogel such as gel fraction percentage (GF%), and swelling percentage (SW%) were investigated. It was found that the GF % decreases with increasing SA content in the hydrogel. While the SW% of CMC/SA hydrogel tends to increase with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…30) [319]. Gamma radiation proved to be very efficient for the crosslinking of polysaccharides, such as carboxymethyl cellulose (CMC) [321], CMC combined with starch [322], acrylic acid and starch [323], CMC and sodium alginate [324], hyaluronic acid and chondroitin sulfate [325] carboxymethylchitosan [326]. The chemical structure and size of the polysaccharide chains, the polysaccharide concentration, radiation dose and atmosphere can affect the crosslinking process.…”
Section: Photocrosslinkingmentioning
confidence: 99%
“…30) [319]. Gamma radiation proved to be very efficient for the crosslinking of polysaccharides, such as carboxymethyl cellulose (CMC) [321], CMC combined with starch [322], acrylic acid and starch [323], CMC and sodium alginate [324], hyaluronic acid and chondroitin sulfate [325] carboxymethylchitosan [326]. The chemical structure and size of the polysaccharide chains, the polysaccharide concentration, radiation dose and atmosphere can affect the crosslinking process.…”
Section: Photocrosslinkingmentioning
confidence: 99%
“…The use of gamma radiation for preparing of different types of adsorbent polymers and hydrogels is considered as wide field of important applications of radiation technology that can be used in environmental applications. [14][15][16][17][18][19][20][21][22] hydrolysed) was provided by Lobachemie Pvt. Ltd, Mumbai, Maharashtra, India.…”
Section: Introductionmentioning
confidence: 99%
“…The use of gamma radiation for preparing of different types of adsorbent polymers and hydrogels is considered as wide field of important applications of radiation technology that can be used in environmental applications. 1422…”
Section: Introductionmentioning
confidence: 99%
“…27 Microcrystalline cellulose (MCC)-based hydrogel loaded with MnO 2 is used to remove lead from wastewater. 28 Carboxymethyl cellulosebased hydrogels like poly(vinyl alcohol)−CMC 25 and CMC− sodium alginate 24 are used to remove Ni(II). Godiya et al reported CMC/polyacrylamide-based hydrogel for the removal of Cd(II) and other metal ions.…”
Section: Introductionmentioning
confidence: 99%